Complement activation negatively affects the platelet response to thrombopoietin receptor agonists in patients with immune thrombocytopenia: a prospective cohort study. (31st December 2023) - Åkesson, Alexander; Bussel, James B.; Martin, Myriam; Blom, Anna M.; Klintman, Jenny; Ghanima, Waleed; Zetterberg, Eva; Garabet, Lamya
Abstract: Increased platelet destruction is central in the pathogenesis of immune thrombocytopenia. However, impaired platelet production is also relevant and its significance underlies the rationale for treatment with thrombopoietin receptor agonists (TPO-RAs). Previous studies have associated enhanced complement activation with increased disease severity. Additionally, treatment refractoriness has been demonstrated to resolve by the administration of complement-targeted therapeutics in a subset of patients. The association between complement activation and the platelet response to TPO-RA therapy has previously not been investigated. In this study, blood samples from patients with immune thrombocytopenia (n = 15) were prospectively collected before and two, six and 12 weeks after the initiation of TPO-RA therapy. Plasma levels of complement degradation product C4d and soluble terminal complement complexes were assessed. Patients with significantly elevated baseline levels of terminal complement complexes exhibited more often an inadequate platelet response ( p = .04), were exclusively subjected to rescue therapy with intravenous immunoglobulin ( p = .02), and did not respond with a significant platelet count increase during the study period. C4d showed a significant ( p = .01) ability to distinguish samples with significant terminal complement activation, implying engagement of the classical complement pathway. In conclusion, elevated levels of complement biomarkers were associated with a worse TPO-RA treatment response. Larger studies are needed to confirm these results. Biomarkers of complement activation may prove valuable as a prognostic tool to predict which patients that potentially could benefit from complement-inhibiting therapy in the future. Plain Language Summary: What is the context? Primary immune thrombocytopenia (ITP) is a potentially serious illness associated with an increased risk of bleeds. Manifestations range from confined skin bruising to life-threatening intracranial hemorrhages. It is an acquired immune disorder characterized by increased destruction and impaired production of platelets. Treatments aim at suppressing the destruction and supporting the production of platelets. Thrombopoietin receptor agonists (TPO-RA) are medically approved platelet growth factors that contribute to the generation of new platelets. The complement system is an evolutionary preserved part of innate immunity. Previous studies have indicated that complement activation may be an important contributor to disease and that the administration of complement-inhibiting therapy improves the platelet count in a subset of patients with primary ITP. What is new? The potential association between complement activation and a poor platelet response to TPO-RA therapy in primary ITP has not been previously studied. In fifteen patients with primary ITP starting TPO-RA therapy, we prospectively followed the platelet response and levels of complement biomarkers for 12 weeks. We showed that patients with high levels of complement biomarkers exhibited a worse treatment response during the study period. What is the impact? Our results suggest that levels of complement biomarkers may be valuable to predict which patients with treatment-refractory ITP that potentially could benefit from complement-inhibiting therapy in the future Larger studies are needed to confirm our results.